(untitled) (Journal of Comparative & International Higher Education, 2024)
This study examined the post-graduation employment location preferences of international students preparing to participate in the Optional Practical Training (OPT) program in the United States. An exploratory survey asked international students in their final semesters at three midwestern public universities to indicate their employment location preferences via an online text- and map-based questionnaire. Two main questions guided the research: 1) Do international students hold employment location preferences prior to graduation? and 2) Where in the United States do international students applying for OPT prefer to work? Results indicated the affirmative and that preference geographies extend well beyond the state in which the students earned their degrees. In applying for OPT, participants in this study signaled their intent to remain in-country. As such, the scale of analysis shifts from traditional country-to-country migration flows of international students to the internal movements within the host country in anticipation of post-graduation employment.